Split otoferlins reunited - Jeffrey R Holt; Gwenaelle SG Geleoc (EMBO Molecular Medicine)
Abstract Gene therapy for genetic hearing loss is a nascent field with just a handful of studies published to date that demonstrate proof‐of‐concept recovery of auditory function (reviewed in Ahmed et al, 2017; Lustig & Akil, 2018). One challenge that faces the inner ear field, as well as the broader gene therapy field, is the need to deliver large gene sequences despite the limited genetic capacity (~4.5 kB) of delivery vehicles such as adeno‐associated viral vectors (AAV). In this issue, Al‐Moyed et al have overcome this conundrum by using two AAV vectors to deliver the coding sequence for otoferlin, which is ~6 kB. With dual‐AAV delivery of split otoferlin and a trans‐splicing approach, they demonstrate recombination of full‐length otoferlin in sensory hair cells of the inner ear, enabling partial restoration of auditory function in deaf, otoferlin‐null mice.